2005
DOI: 10.1074/jbc.m411617200
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Amyloid-like Assembly of the Polypeptide Sequence Coded by Exon 30 of Human Tropoelastin

Abstract: Elastin is known to self-aggregate in twisted-rope filaments. However, an ultrastructural organization different from the fibrils typical of elastin, but rather similar to those shown by amyloid networks, is shown by the polypeptide sequence encoded by exon 30 of human tropoelastin. To better understand the molecular properties of this sequence to give amyloid fibers, we used CD, NMR, and FTIR (Fourier transform infrared spectroscopy) to identify the structural characteristics of the peptide. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 58 publications
(53 reference statements)
8
81
0
1
Order By: Relevance
“…Each fibril was found to be composed of many polypeptide molecules (Fig. 2b), which is in line with previous reports suggesting that amyloid-like fibrils are likely to originate from extensive self-interactions of elemental cross ␤-structures (19). We also were able to observe fine structural features of the fibrils, such as the characteristic helical twist.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Each fibril was found to be composed of many polypeptide molecules (Fig. 2b), which is in line with previous reports suggesting that amyloid-like fibrils are likely to originate from extensive self-interactions of elemental cross ␤-structures (19). We also were able to observe fine structural features of the fibrils, such as the characteristic helical twist.…”
Section: Resultssupporting
confidence: 78%
“…It may be possible that the aggregation into such well defined, nanoordered assemblies represents a state of an efficient minimal energy arrangement of polypeptide chains (15)(16)(17). Recent results have shown that fibrillar structures similar to amyloid fibrils are formed by sequences like poly(XGlyGlyYGly) (X, Y ϭ Val, Leu, or Ala), which are highly repeated in the hydrophobic domains of elastin (18,19).…”
Section: Charge Transport and Intrinsic Fluorescence In Amyloid-like mentioning
confidence: 99%
“…3B) (17,29). Exceptions to this were EP20-P12-P12, EP20-24-P6N, and EP20-P6N-P6N, which all contained prominent peaks at 1625 cm Ϫ1 usually associated with ␤-sheet (17,25,27), suggesting that these polypeptides were relatively susceptible to the formation of such ␤-structures.…”
Section: Distribution Of Proline Residues In Hydrophobic Sequencesmentioning
confidence: 99%
“…Tropoelastin forms coacervates at temperatures above its LCST, and it is thought that this behavior is partially responsible for elastin's ability to form fibrils [31][32][33]203]. In addition, Tamburro et al have conducted many studies on the structures of tropoelastin, and their results provide further insight into the role secondary structure has on to the self-assembly of elastin fibers [204][205][206][207].…”
Section: Human Tropoelastin-based Polypeptidesmentioning
confidence: 99%